Crop residues and fertility - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
A research programme sponsored by the International Union of Biological Sciences (IUBS) and UNESCO is investigating how organic matter in tropical soils breaks down. This knowledge is of vital importance to farmers in the tropics who have little...